Accounting graduates’ competences - Ika Prayanthi; Melinda Lydia Nelwan (Jurnal Akuntansi dan Auditing Indonesia, 2019)
This study aimed to find out the competence needed by fresh graduates based on the perceptions of acounting practitioners. This study used a combination of qualitative and quantitative methods and used the statistical technique of exploratory factor analysis. A qualitative method was used in identifying variables to be studied, while quantitative method was used in grouping or categorizing of those variables into certain factors. This study used 40 variables developed based on the interview results and questionnaires filled by 100 respondents consisting of accounting practitioners namely those who worked in accounting and finance deparment starting from staff level up to financial directors spread across various companies in Indonesia. The results of the study found eight main competencies that should be possessed by accounting students based on the perceptions of the employers. Those competencies were (1) work ethics, (2) interpersonal skills, (3) good leadership, (4) responsibility, (5) analytical ability, (6) skills, (7) ability to adapt, and (8) work experience.